Analisis Yuridis Konsep Pemilihan Umum Serentak di Indonesia - Lusin Tammu (Universitas Medan Area, 2023)
This study aims to analyyze the Regulasion for the Birth of the Simultaneous General Election Concept in terms of contitutional interpretation and the choices of the Simultaneous General Election implementation model as alternative model for holding contitusional election in accordance with the decisions of the constitutional court. The type of research used is normative research. The approach used is a statutory approach and a conceptual approach. The legal materials used are primary legal materials, and tertiary legal materials.The results of this study indicate that the birth of the Simultaneous General Election Regulation as well as from a historical interpretation point of view, namely based on discussions in the amendements in the 1945 constitution and the original intent wanted the birth of the election concept with a five ballot box model, the Simultaneous General Election that are considered constitutional and the ideal model from various perspectives is the implementation of local and national elections.